O financiamento no contexto das políticas de municipalização da educação básica: um estudo sobre o município de Concórdia-SC - Baseggio, Tayson Sander (2023)
The present di ssertation focuses on the study of policies and dynamics of financi ng for municipal basic education in the city of Concórdia (SC) from 2010 to 2021. The study aimed to (i) analyze the main policies for financing ba sic education in Brazil; (ii) understand t he main changes that the new FUNDEB (EC 108/20) introduced in the r egime of financing basic education in Brazil; (iii) analyze how the policies of municipalization and financing redefined municipal basic education in Concórdia; (iv) analyze the revenue and investments in basic education of the municipal public network in Concórdia (SC). In addition to bibliographic and documentary research on policies for financing basic education at the national and local levels, t he study relied on extensive data collecti on and qualitative analysis available in the INEP (School Census), SIOPE, FNDE databases, and the Transparency Portal in the Municipal Government of Concórdia. The research showed, among other results, that the pol icies of centralization and municipalizati on of basic education implemented from the 1990s onwards promoted a significant reduction in the number of rural schools and, consequently, an increase in enrollments in urban areas. Municipalization policies also led to a significant growth of the municip al education network. In 2010, the municipal network in Concórdia a ccounted for 46.89% of enrollments in basic education. In 2021, the percentage increased to 55.67% of enrollments. Regarding financing, the study f ound an increase in resources from the Fun d for Maintenance and Development of Basic Education (FUNDEB) and t he National Fund for the Development of Education (FNDE). Between 2010 and 2021, the FNDE transfer to the municipal network in Concórdia increased by 48.3%. The resources received from FUND EB also increased by about 60.96% during the same period. The avera ge investment per student in the municipal network also grew, from R$ 6,656.37 in 2010 to R$ 10,607.21 in 2021, a 59.35% increase. The research als o highlighted the impacts of Constitutiona l Amendment No. 95 and the Covid 19 pandemic on the budget of munic ipal education. In 2020, for example, there was a 3.6% decrease in FUNDEB revenues and a 12% decrease in resources from FNDE.